Influence of Coal Bottom Ash on Properties of Portland cement Mortar - Ibrahim, Ali Huddin (International Journal of Integrated Engineering, 2019)
In this study, the effects of coal bottom ash (CBA) on the properties of Portland cement mortar were investigated. Mortars with different proportions (cement: sand ratios) of 1:2.5 and 1:2.75 were prepared where the CBA was used to partially substitute the Portland cement. The influence of the CBA inclusion on the properties of the mortars, namely flow, compressive strength, porosity, water absorption and gas permeability was evaluated and compared with the reference mortar mixtures. The results showed that the use of CBA as partial Portland cement replacement material had clear influences on the investigated properties of the mortars. The use of CBA reduced the measured flow values of the fresh mortars, with higher reduction at higher CBA content. The effect of the CBA inclusion at 10 and 20% for the 1:2.5 mortar mixture and at 10% for the 1:2.75 mortar mixture increased the strength, but reduced the porosity, water absorption and permeability at longer curing periods of 28, 56 and 90 days. The overall results of the study portray that the CBA has the potential to be used to partially replace Portland cement in the production of mortar and concrete.